Marital and Parental Status and Quality of Life of Female Clerical Workers - Kahn, Sharon E.; Long, Bonita C.; Peterson, Christine (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examines marital and parental status in relation to perceptions of the quality of work and family roles (psychological well-being, job satisfaction, work involvement, nonoccupational environment, and role demands) in 148 female clerical workers. Discriminate function analysis was used to identify variables which discriminate among married and single women and women with and without children. Results showed that income differentiates married and unmarried women and the presence of school-age children relates to greater role demands. No differences were found among other variables. These results are discussed in relation to employed women's multiple roles and vocational counselling issues.